2019
DOI: 10.1111/ocr.12291
|View full text |Cite
|
Sign up to set email alerts
|

3D Airway changes using CBCT in patients following mandibular setback surgery ± maxillary advancement

Abstract: Structured Abstract Introduction The aim of this study was to determine the 3D airway changes that occur following mandibular setback surgery alone vs bimaxillary surgery in patients with similar skeletal start forms. Setting and Sample Population The University of Michigan School of Dentistry and Medical Center. A total of 85 patients undergoing mandibular setback with or without simultaneous maxillary advancement. Materials and Methods A retrospective evaluation of pre‐ and post‐surgical CBCT scans for patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
1
10
0
1
Order By: Relevance
“…In the current study, our results showed decrease in surface area post-operatively in both groups with no statistically significant difference was observed. This was in agreement with He et al (31) and Hsieh et al (37) , Who found the minimum cross-sectional area of the upper airway was narrower 6 months after bimaxillary surgery, while in consistent with Havron et al (36) who found that statistically significant increases in the axial areas at both C1 (retropalatal region) and C2 (retroglossal region) in the group underwent mandibular setback with maxillary advancement.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the current study, our results showed decrease in surface area post-operatively in both groups with no statistically significant difference was observed. This was in agreement with He et al (31) and Hsieh et al (37) , Who found the minimum cross-sectional area of the upper airway was narrower 6 months after bimaxillary surgery, while in consistent with Havron et al (36) who found that statistically significant increases in the axial areas at both C1 (retropalatal region) and C2 (retroglossal region) in the group underwent mandibular setback with maxillary advancement.…”
Section: Discussionsupporting
confidence: 90%
“…. following orthognathic surgeries (12,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) may be attributed to many factors as the complexity of the airway and it's response after different surgeries, differences imaging modalities (2, 3, 5-7, 10) in addition to pharyngeal airway segmentation limits (20)(21) and follow-up time (42) .Each study, including the present one, used unique amount movements and positioning of the maxilla and mandible besides simple anterior or posterior repositioning, Superior movements or rotations. All these asymmetric changes make uniform evaluation impossible, and all these factors lead to different results obtained.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Specifically, significantly more orthognathic patients report a perceived improvement in breathing through maxillary advancement (with or without mandibular setback) (95%) than with mandibular setback alone (56%) [ 5 ]. Bimaxillary surgery results in greater increases than mandibular setback in the volume of the airway, which are primarily apparent due to an increase in the retropalatal region [ 6 ]. For growing Class III patients, orthopedic appliances are sometimes used to protract the maxilla, restrict or redirect mandibular growth, or both, while at the same time, both approaches lead to a mandibular rotation.…”
Section: Introductionmentioning
confidence: 99%
“…Back in 2012, Van Vlijmen, based on the then‐available evidence, could claim that only the studies assessing airway diagnostics showed a scientific impact of CBCT in the orthodontic field 3 . Different aspects were analysed by other authors: effects produced by conventional fixed appliance therapy and/or orthognathic surgery, effects produced by extractive treatments and outcomes generated by functional appliance therapy 4‐10 . Among them, a special interest was devoted to the possible relationships between airway dimensions and different anteroposterior facial patterns 11‐18 .…”
Section: Introductionmentioning
confidence: 99%